Theo đề bài :
\(\left(36:a-a\right):a-a=-a\)
\(\Rightarrow\left(36:a-a\right):a=-a+a=0\)
\(\Rightarrow36:a-a=0.a=0\)
\(\Rightarrow36:a=0+a=a\)
\(\Rightarrow36=a.a=a^2\)
\(\Rightarrow\left[\begin{array}{nghiempt}a=6\\a=-6\end{array}\right.\)
Theo đề bài ta có:36:(a-a):(a-a)=-a
36:1=-a
36=-a
Vậy a=-36
Theo bài ra , ta có :
( 36 : a - a ) : a - a = - a
=> ( 36 : a - a ) : a = ( - a ) + a
=> ( 36 : a - a ) : a = 0
=> 36 : a - a = 0 x a
=> 36 : a - a = 0
=> 36 : a = 0 + a
=> 36 : a = a
=> 36 = a . a
=> 36 = a2
<=> \(\left[\begin{array}{nghiempt}a=6\\a=-6\end{array}\right.\)
Vậy a \(\in\) { -6 ; 6 }